Olympiad Movement in the System of Partnership "School-University-Enterprise" - D. A. Troeshestova (Moscow Polytechnic University, 2019)
The article addresses the problem of organizing Olympiads and competitions for schoolchildren and students by the University to identify and support them in their individual educational and career trajectory, with the participation of employers in the region. To solve this problem, I.N. Ulianov Chuvash State University is implementing a number of projects in the partnership system «school - University - enterprise». The article highlights the activities of the Centre for working with the talented youth of I.N. Ulianov Chuvash State University aimed at realization of the strategic project roadmap of the University «Formation and development of the complex for popularization of promising careers, engaging and support of the talented youth in the system of multilevel anticipatory staff training». The article describes a unique experience in organizing academic Olympiads and creative design contests for schoolchildren in conjunction with innovative enterprises of the Chuvash Republic, among which are: «Hope of Chuvashia electrical engineering», «Hope of Chuvashia mechanical engineering», «Builders of the future », «Electronics 4.0», «IT-Ring». Winners and prizeholders of these academic Olympiads and contests get involved into the work of professional navigational guidance platform of the University «Center for career planning». Currently, the University is actively working on adaptation and introduction of the tutorship model. Key indicators of Olympiad movement efficiency in the network of cooperation with enterprises are provided. An analysis of these indicators makes it possible to conclude that various academic Olympiads and competitive activities for schoolchildren held together with enterprises-partners increase the number of winners and prize-holders of the highest level academic Olympiads entering the University. The article also discusses the forms of supplementary education for gifted schoolchildren and their teachers-tutors. It is stated that the value is not holding Olympiads and identifying talented schoolchildren, but regular classes with them in clubs and in supplementary education courses. It is concluded that by attracting talented graduates of secondary educational institutions to enter the University and their active participation in student Olympiad movement organized in partnership with leading innovative enterprises, the problem of professional elite developing in the region is successfully being solved.